Evidence Review Conducted for the Agency for Healthcare Research and Quality Safety Program for Improving Surgical Care and Recovery: Focus on Anesthesiology for Total Knee Arthroplasty. (March 2019) - Soffin, Ellen M.; Gibbons, Melinda M.; Ko, Clifford Y.; Kates, Stephen L.; Wick, Elizabeth; Cannesson, Maxime; Scott, Michael J.; Wu, Christopher L.
Abstract : Enhanced recovery after surgery (ERAS) has rapidly gained popularity in a variety of surgical subspecialities. A large body of literature suggests that ERAS leads to superior outcomes, improved patient satisfaction, reduced length of hospital stay, and cost benefits, without affecting rates of readmission after surgery. These patterns have been described for patients undergoing elective total knee arthroplasty (TKA); however, adoption of ERAS to orthopedic surgery has lagged behind other surgical disciplines. The Agency for Healthcare Research and Quality, in partnership with the American College of Surgeons and the Johns Hopkins Medicine Armstrong Institute (AI) for Patient Safety and Quality, has developed the Safety Program for Improving Surgical Care and Recovery. The program comprises a national effort to incorporate best practice in perioperative care and improve patient safety, for over 750 hospitals and multiple procedures over the next 5 years, including orthopedic surgery. We have conducted a full evidence review of anesthetic interventions to derive anesthesiology-related components of an evidence-based ERAS pathway for TKA. A PubMed search was performed for each protocol component, focusing on the highest levels of evidence in the literature. Search findings are summarized in narrative format. Anesthesiology components of care were identified and evaluated across the pre-, intra-, and postoperative phases. A summary of the best available evidence, together with recommendations for inclusion in ERAS protocols for TKA, is provided. There is extensive evidence in the literature, and from society guidelines to support the Agency for Healthcare Research and Quality Safety Program for Improving Surgical Care and Recovery goals for TKA.